Assessment of soil hardness expressed by one drop penetrability at forest restoration sites along Kayan Ulu river, Sarawak, Malaysia - Aina Nadia Najwa, Mohamad Jaffar; Mohd Effendi, Wasli; Mugunthan, Perumal; Hamsawi, Sani; Jonathan, Lat (2018)
Soil hardness measurement is recommendable for comprehensive understanding of the soil conditions prevailing in degraded tropical forests. Restoration trials have demonstrated a wide variety of edaphic and climatic conditions by using indigenous species. The aim of this study is to restore the riverbank ecosystem by evaluating the soil condition of forest restoration sites along Kayan Ulu river with special reference to soil hardness. Soil hardness was measured by using Hasegawa-type cone penetrometer from the soil surface to 100 cm depth, with a total of 48 random points for both study sites surveyed; restoration sites planted with Shorea macrophylla in year 1996 and 1998 (SPD96 and SPD98, respectively). Our findings indicated that, soil hardness in SPD98 was harder as compared to SPD96, in which higher frequency of soil hardness was encountered in SPD98 with a total of 126 strikes as compared to SPD96 with 117 strikes. High compaction of soils was presumably due to the accumulation of stagnant water adjacent the river and presence of gravel materials which inhibits tree roots to penetrate into soils. Further studies on other environmental factors such as microclimate, soil biological properties and weed competition should be implemented to draw up a Dipterocarp planting scheme for future restoration of riverbanks ecosystem in the tropics.